ILMU SOSIAL, BUDAYA INTELEKTUAL DAN SEMANGAT KENABIAN: TELAAH PENGEMBANGAN ILMU SOSIAL NUSANTARA - Jurdi, Syarifuddin (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2017)
Indonesiaorin the cultural language is called by the Nusantara is a region stretching from Sabang to Merauke, includes various islands, customs, language, religion, culture and social traditions. This article attempts to lay the objective conditions of the development of social sciences of the Nusantara and the possible development of a typical Indonesian social sciences.The social sciences here are conceptualized from the social and cultural traditions of Indonesia itself. Conceptualisation of social science should be synergic between the spirit of the development of the science of its scientists and support countries on another hand, of course, the development ofsocial sciences in the future by the political partiality of state accompanied by incorporating cultural values as lecture material. Withsocialhistoricalparse, this article presents a discussion about the historicity of social sciences, forming the intellectual block, institutionalization ofsocial sciences in the Nusantara and its reflection, and theÂ prophetic spirit and intellectual asceticism.